2014
DOI: 10.1371/journal.ppat.1004197
|View full text |Cite
|
Sign up to set email alerts
|

The Calcium-Dependent Protein Kinase 3 of Toxoplasma Influences Basal Calcium Levels and Functions beyond Egress as Revealed by Quantitative Phosphoproteome Analysis

Abstract: Calcium-dependent protein kinases (CDPKs) are conserved in plants and apicomplexan parasites. In Toxoplasma gondii, TgCDPK3 regulates parasite egress from the host cell in the presence of a calcium-ionophore. The targets and the pathways that the kinase controls, however, are not known. To identify pathways regulated by TgCDPK3, we measured relative phosphorylation site usage in wild type and TgCDPK3 mutant and knock-out parasites by quantitative mass-spectrometry using stable isotope-labeling with amino acids… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

8
99
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 71 publications
(109 citation statements)
references
References 53 publications
(77 reference statements)
8
99
2
Order By: Relevance
“…For example, loss of TgCDPK3 also affects parasite egress, and under some conditions microneme secretion and motility (23). Recent studies indicate that TgCDPK3 acts upstream of TgCDPK1 by controlling calcium homeostasis, and consistent with this, TgCDPK1 overexpression can partially compensate for loss of CDPK3 (24). Although both TgCDPK1 and TgCDPK3 regulate egress in T. gondii, this function is provided by CDPK5 in P. falciparum (25).…”
Section: -Isoleucine [I]-lysine [K]-lysine [K]) Kinases In Plasmodiummentioning
confidence: 91%
See 1 more Smart Citation
“…For example, loss of TgCDPK3 also affects parasite egress, and under some conditions microneme secretion and motility (23). Recent studies indicate that TgCDPK3 acts upstream of TgCDPK1 by controlling calcium homeostasis, and consistent with this, TgCDPK1 overexpression can partially compensate for loss of CDPK3 (24). Although both TgCDPK1 and TgCDPK3 regulate egress in T. gondii, this function is provided by CDPK5 in P. falciparum (25).…”
Section: -Isoleucine [I]-lysine [K]-lysine [K]) Kinases In Plasmodiummentioning
confidence: 91%
“…Previous studies with other CDPKs have shown that in some cases they can compensate for each other or that they work in common pathways (23,24). Hence, we considered that the lack of phenotypes for noncanonical CDPKs might reflect redundant functions such that single-gene knockouts remain normal.…”
Section: Sequence and Expression Analyses Of Noncanonical Cdpks In Tmentioning
confidence: 99%
“…For example, the functions of TgCDPK3 partially mimic those of TgCDPK1 and they can also be compensated for by activation of protein kinase G (PKG), a distinct kinase that is also required for both egress and entry of T. gondii 29, 42 . Recent studies implicate TgCDPK3 in control of calcium homeostasis, suggesting that it acts upstream of TgCDPK1 43 . Consistent with this finding, over-expression of TgCDPK1 can partially rescue the egress phenotype of Δ cdpk3 mutants 43 .…”
Section: Biology Of Cdpksmentioning
confidence: 99%
“…This study revealed 700 phosphopeptides, including unreported phosphosites corresponding to proteins involved in cellular polarization and mating tip formation [33]. More recently, SCX/IMAC-based phosphoproteomic studies resulted in the identification of more than 13,000 phosphorylation sites in fly embryos [34], over 13,000 in the parasite Toxoplasma gondii [35] and nearly 36,000 unique phosphosites in 9 mouse tissues [36].…”
mentioning
confidence: 95%